Best Algorithms + Best Computers = Powerful Match. (Communications of the ACM, 2012)
The article introduces a paper concerning the efficient parallelization of an algorithm that exploits hierarchical representation of the forces that can be used for scientific computations that are too large or complex to be solved on a single processor.